2013
DOI: 10.1017/s1431927613012695
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Electron-Probe Microanalysis of Fe–Si Compounds Using Soft X-Rays

Abstract: Conventional electron-probe microanalysis has an X-ray analytical spatial resolution on the order of 1-4 μm width/depth. Many of the naturally occurring Fe-Si compounds analyzed in this study are smaller than 1 μm in size, requiring the use of lower accelerating potentials and nonstandard X-ray lines for analysis. Problems with the use of low-energy X-ray lines (soft X-rays) of iron for quantitative analyses are discussed and a review is given of the alternative X-ray lines that may be used for iron at or belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 23 publications
3
68
0
Order By: Relevance
“…One solution to the quantification problems of Ni-silicides at low voltage is to use the Ni-Ll line, as has already been suggested by [8][9][10]. The Ll-line, with an energy of 742 eV, is far from the L 2,3 -absorption edges, and corresponds to a radiative transition (L 3 -M 1 ) that does not involve the unfilled 3d-shell.…”
Section: K-ratios Using the Ni-ll Line And Conventional Macsmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution to the quantification problems of Ni-silicides at low voltage is to use the Ni-Ll line, as has already been suggested by [8][9][10]. The Ll-line, with an energy of 742 eV, is far from the L 2,3 -absorption edges, and corresponds to a radiative transition (L 3 -M 1 ) that does not involve the unfilled 3d-shell.…”
Section: K-ratios Using the Ni-ll Line And Conventional Macsmentioning
confidence: 99%
“…Gopon et al [8] showed that the use of the less intense Ll (L 3 -M 1 transition) line, which does not involve transitions from the unfilled 3d-shells, may be a suitable alternative for the analysis of Fe-silicides at low voltage. Statham and Holland [9] also used the Ll-lines to analyse a high Cr-Ni steel.…”
Section: Introductionmentioning
confidence: 99%
“…Gopon et al [1] showed that the Fe Ll line had some utility, but its weak intensity was a drawback. Here we investigate the possible utility of Fe Lα and Lβ.…”
mentioning
confidence: 99%
“…Due to the strong absorption of these lines in the high-energy side by the L2 and L3 absorption edges, the peak shapes are not symmetrical and a sum of pseudo-Voigt function is needed to ensure a good fitting. The MACs were obtained by non-linear fitting of the previously obtained L line intensities in relation to the accelerating voltage using the PAP model [1] The variations of the MAC in relation to the photon energy can be evaluated with the self-absorption spectrum which is constructed by comparing the spectrum acquired at 2.5 kV with the spectrum acquired at 30 kV. As seen in Figure 1, the self-absorption spectra measured on pure Fe and on fayalite differ greatly.…”
mentioning
confidence: 99%
“…During the initial analysis of Fe-Si [6], it was suggested that carbon (~1-2 wt. %, determined by EPMA) might be present in the Fe-Si, but the possibility of analytical artifacts has not been resolved.…”
mentioning
confidence: 99%